PENGEMBANGAN STRATEGI PEMASARAN PRODUK AYAM KRISPI FROZEN CHICKENESIA DALAM MENINGKATKAN OMSET PENJUALAN - Amelia, Reski; Nurliani, Nurliani; Ilsan, Mais (JURNAL AGRIMANSION, 2025)
Ayam krispi frozen is a crispy chicken processed food through the process of frying or roasting, then frozen to maintain freshness, facilitate storage and distribution. This research aims to: 1) describe the marketing strategy of chickenesia frozen krispi chicken products, 2) calculate the impact of marketing strategy development on the sales turnover of chickenesia frozen krispi chicken, and 3) gain valuable knowledge, skills and insights. The approach method uses the “lean startup” method. Data analysis used descriptive qualitative and quantitative analysis based on entrepreneurial prototypes to describe process performance and outcome performance. The results showed that the marketing process of frozen chickenesia crispy chicken products went through 3 (three) stages, namely the preparation, implementation and evaluation/monitoring stages. The marketing strategies developed are business-to-business (B2B) and business-to-consumer (B2C) strategies. The business-to-business (B2B) strategy successfully reached the segment of housewives who wanted to start a small business, while the business-to-consumer (B2C) strategy effectively attracted teenagers, students, and employees as end consumers. The marketing strategies implemented proved to be able to increase product competitiveness and expand market reach. In addition, this activity has a positive impact on the cognitive ability of market analysis and business communication, affective development (soft skills) and conative ability.